CHILDHOOD IN THE DISCOURSE OF HUMANITARIAN STUDIES AT THE BEGINNING OF THE XXI CENTERY - Kvas, Olena (Mountain School of Ukrainian Carpaty, 2022)
The aim of the study is to analyze the modern scientific discourse of research on childhood problems. The article examines the peculiarities of the interpretation of the phenomenon of childhood at the turn of the century. It has been established that modern researchers of childhood interpret it mostly through traditional academic discourses, which consist in the division of childhood between psychology, sociology and anthropology. The peculiarities of the interdisciplinary approach in the process of childhood research are revealed, which refers to the integrated methodology of studying problems related to the life of children and their protection, which, in its turn, forms the modern interpretation of "the child in context". This vision of childhood allows us to consider it as one of the priorities of state policy in many countries of the world. The research substantiates the idea that the problem of childhood in modern social sciences is quite often defined as a direction that largely consists in traditional theorizing and recognition of a large number of means of social construction and reconstruction of childhood, depending on time and place, age and gender, ethnic and religious differences, etc. The concept of "child", which refers to an "immature" personality, has been studied; at the same time, the concept of "childhood" is more general and abstract and indicates the status of those who are called minors. In particular, it is outlined that adulthood can be defined through physical or sexual maturity, sometimes through legal capacity. We can state that the term "childhood" focuses mainly on the child's state of being, without having to do with an individual child; it assumes the existence of a distinct, separate, fundamentally different social category – "childhood". However, the most difficult task remains to find out to what extent critical stages of social life, changes and trends belong to the research field and academic discourse of childhood and how much they reflect and characterize the patterns of development of social sciences, as well as paradigmatic changes in pedagogy.